2000
DOI: 10.1001/archsurg.135.11.1285
|View full text |Cite
|
Sign up to set email alerts
|

Echogenicity of Liver Metastases Is an Independent Prognostic Factor After Potentially Curative Treatment

Abstract: Hypothesis: Intraoperative echogenic appearance of liver metastases from colorectal cancer is a prognostic factor of outcome after curative treatment. Design: Retrospective analysis of prospectively collected data. Setting: Department of Surgery at a university hospital. Patients: One hundred forty-three consecutive patients with hepatic metastases from colorectal cancer who underwent liver resection with curative intent between 1992 and 1998. Intervention: Curative treatment was achieved by liver resection al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Currently, there are few data on the IOUS characteristics of colorectal liver metastases. The few previous studies [13][14][15] that have examined the echogenicity of colorectal liver metastasis reported that the majority (54%-65%) of colorectal liver metastases were hyperechoic in nature. In contrast, in the current study, most colorectal liver metastases were found to be hypoechoic (52.0%).…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are few data on the IOUS characteristics of colorectal liver metastases. The few previous studies [13][14][15] that have examined the echogenicity of colorectal liver metastasis reported that the majority (54%-65%) of colorectal liver metastases were hyperechoic in nature. In contrast, in the current study, most colorectal liver metastases were found to be hypoechoic (52.0%).…”
Section: Commentmentioning
confidence: 99%
“…Colorectal metastases can appear hypoechoic, isoechoic, or hyperechoic in comparison with the surrounding liver tissue. [13][14][15] The echogenicity of the metastasis can influence the surgeon's ability to detect lesions on IOUS because isoechoic…”
mentioning
confidence: 99%
“…Other investigators have suggested that hypoechoic lesions were significantly more likely to be mucinproducing tumors. 10 Mucin secretion is an established negative prognostic factor for primary colorectal cancer. 26,27 In the current study, we similarly noted that hypoechoic lesions were more likely to be mucin-producing, although this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature have shown that after the surgical treatment of the primary tumor, the ultrasound of metastasis after colorectal cancer can be correlated with prognosis. Thus, Gruenberger et al [52] demonstrated that in patients with hyperechoic ultrasound liver metastases, survival is longer than in those with the hypoechoic aspect of the lesions. This suggests that the role of IOUS is more than a diagnostic one and can be useful in establishing prognosis [53].…”
Section: Liver Research and Clinical Managementmentioning
confidence: 99%